Analysis Of The Application Of Resource-Based View Theory To Develop An Agile Strategy (Case Study At ABC SME) - Elza Roselin Hutapea; Hilda Rossieta (UNIVED Press, 2026)
This study aims to analyze the application of Resource-Based View (RBV) in building agile strategies in MSMEs to face the challenges of the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era. The study was conducted on MSME ABC, a convection business that transformed from a B2B model to a combination of B2B and B2C in response to the dynamics of the business environment. A qualitative approach was used through a case study, with data collected through observation, in-depth interviews, analysis of customer reviews on e-commerce, and distribution of questionnaires to management and employees. The analysis was conducted with the RBV framework using the VRIO (Valuable, Rare, Inimitable, Organized) approach and the Agile Wheels concept (Gunasekaran, 2001). Of the 20 resources and capabilities of MSME ABC, five provide sustainable competitive advantages, while the rest are temporary. Key challenges include supply chain disruptions, technological limitations, lack of innovation, weak customer understanding, and low financial management capacity. The study recommends an agile strategy through strengthening adaptive internal processes, increasing external linkages with customers and suppliers, and developing human resource capabilities. These findings provide theoretical contributions to strengthening resource-based strategies and practical benefits for increasing the competitiveness of MSMEs amidst market uncertainty.